Behavioral and physiological differences of dry dairy cattle under heat stress based on median core body temperature - Fritz, Rebecca (Kansas State University, 2021)
Heat stress has been demonstrated to have implications on the profitability of the dairy industry. The objectives of this observational study were to investigate behavioral differences of dairy cows having above or below the median core body temperature (CBT) assessed during 1 wk during late gestation as well as measure differences in pregnancy-associated glycoprotein (PAG) concentration. Temperature data were collected every 5 min for 7 d using a temperature logger attached to a intravaginal insert between d 220 and 241 of gestation. Within each of 5 replicates, cows having above median CBT were classified as high temperature (HT) and those below median CBT were classified as low temperature (LT). Behavioral data from 50 cows (10 cows per replicate) were collected using automated activity monitors equipped with accelerometers in addition to visual observations. Accelerometer data were evaluated from d -21 to 21 relative to actual calving date. Cows were observed for 8 h in the far-off pen and 8 h in the close-up pen. Each 8-h observation block consisted of two, 2-h morning observations (0600 to 0800 h) and two, 2-h afternoon observations (1600 to 1800 h). At enrollment, cows were between 220 and 241 days of gestation. Blood samples were collected weekly for 3 wk starting at enrollment. No differences were detected among visually observed behaviors during morning or afternoon observations in the far-off or close-up period. An interaction of temperature and parity (P = 0.02) revealed that HT primiparous cows spent the most time eating during afternoon visual observations (30.9%) followed by LT multiparous cows (25.4%), LT primiparous cows (22.5%), and finally HT multiparous cows spent the least time eating (19%). Accelerometer data demonstrated that HT cows had more (P < 0.01) high activity time than LT cows. Compared with primiparous cows, multiparous cows spent more time active during both prepartum (P = 0.02) and postpartum (P < 0.01) periods. High temperature cows were more (P < 0.01) inactive than LT cows before calving. Cows classified as HT had greater (P = 0.05) blood concentrations of PAG during the first 3 wk of the far-off dry period than cows classified as LT. In conclusion, HT and LT cows display different behavior and have different PAG concentrations; however, more research is needed to identify specific thresholds to classify cows as HT and LT.
Keywords: Reproduction; Dairy cow; Behavior; Temperature